Long-Term Follow-up after Kidney Trauma at Prof. Dr. R. D. Kandou General Hospital Manado - Arianto, Eko; Panelewen, Bryan P.; Astram, Ari; Toreh, Christof; Wihono, Frendy (Universitas Sam Ratulangi, 2025)
Abstract: Renal trauma, caused by blunt or penetrating injuries, is associated with severe complications such as hypertension, chronic kidney disease (CKD), and pyelonephritis, especially in high-grade renal trauma. The study aimed to evaluate the complications and management of renal trauma patients at Prof. Dr. R. D. Kandou Hospital Manado from January 2022 to October 2024. This was an observational study with a cross-sectional design involving 17 patients that met the inclusion criteria. Data included types of trauma, severity level, management approaches, and post-trauma complications. Trauma severity was classified using the American Association for Surgery of Trauma (AAST) grading system. The results showed that 58.8% of patients had penetrating trauma, while 41.2% experienced blunt trauma. The highest percentages were found in grade II severity (29.4%). Operative management was the most common approach (58.8%). Post-trauma complications included CKD (70.5%), hypertension (29.4%), and pyelonephritis (29.4%). In conclusion, renal trauma, whether blunt or penetrating, often leads to significant complications such as CKD and hypertension. Proper long-term management and monitoring of kidney function and blood pressure are crucial to minimize the complications. This study highlights the need for early and effective intervention in high-grade renal trauma cases. Keywords: renal trauma; hypertension; acute kidney injury (AKI); chronic kidney disease (CKD); post-trauma complications